Influence of Oleic Acid–Treated LaF3 Nanoparticles as an Additive on Extreme Pressure Properties of Various Grades of Polyalphaolefins - Kumar H.; Harsha A.P. (My University, 2025)
The present work focused on the extreme pressure characteristics of different grades of polyalphaolefins (i.e., PAO 4, PAO 6, PAO 40, and PAO 100) with LaF3 nanoparticles as an additive. The LaF3 nanoparticles were synthesized by the sol-gel method and modified with oleic acid. The synthesized nanoparticles were characterized with various analytical tools, viz. X-ray diffractometry (XRD), high-resolution transmission electron microscopy (HR-TEM), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). Varying doses (0.025–0.15 wt%) of synthesized nanoparticles were blended in all PAOs to prepare nanolubricants. The extreme pressure (EP) properties of nanolubricants were measured using a four-ball tester as per ASTM D2783 to find the last nonseizure load (LNSL), initial seizure load (ISL), just before weld load (JBWL), weld load (WL), and load wear index (LWI). The results revealed that the incorporation of LaF3 nanoparticles efficiently enhanced the EP properties of all PAOs. However, 0.15 wt% of additive was the optimum dose in all PAOs, demonstrating the best EP behavior; that is, the highest LWI and lowest wear scar diameter (WSD) at ISL and JBWL. Numerous characterization techniques such as scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and scan probe microscopy (SPM) were adopted to investigate the probabilistic rationale for the improvement in EP properties. © 2021 Society of Tribologists and Lubrication Engineers.